Isolated Supraclavicular Lymph Node Metastasis in Pancreatic Adenocarcinoma: A Report of Three Cases and Review of the Literature - Soman, Arundhati D; Collins, Joseph M; DePetris, Giovanni; Decker, G Anton; Silva, Alvin; Moss, Adyr; Greer, Wendy; Ashman, Jonathan; Callister, Matthew; Borad, Mitesh J (JOP. Journal of the Pancreas, 2010)
Context Supraclavicular lymph nodes represent a rare site of metastasis in pancreatic cancer. We report three cases of pancreatic adenocarcinoma with metastases to supraclavicular lymph nodes. Case report A 51-year-old male was diagnosed with locally advanced pancreatic adenocarcinoma on computed tomography (CT) scan. He was recommended neoadjuvant chemotherapy followed by chemoradiation therapy. However, positron emission tomography (PET)/CT scans and subsequent fine needle aspiration cytology showed supraclavicular lymph node metastasis. The patient received systemic chemotherapy for metastatic pancreatic adenocarcinoma. The second patient, a 66-year-old female with pancreatic adenocarcinoma, underwent pancreaticoduodenectomy and was found to have peripancreatic lymph node involvement. She received adjuvant chemotherapy and was followed-up with surveillance CT scans, which did not reveal any metastasis. However, the patient complained of neck swelling. PET/CT scan and biopsy revealed supraclavicular lymph node metastasis from a pancreatic adenocarcinoma primary. The third patient, a 79-year-old male with a past history of thyroid carcinoma who was treated with partial thyroidectomy, developed neck swelling 4 years after his surgery. Fine needle aspiration cytology was consistent with known papillary thyroid carcinoma. Staging evaluations revealed a pancreatic mass for which he underwent subtotal pancreatectomy and splenectomy. Histopathology revealed grade 3 pancreatic adenocarcinoma. Excisional biopsy of a supraclavicular lymph node showed metastatic pancreatic adenocarcinoma. PET/CT results were consistent with these findings. Conclusion In patients with pancreatic adenocarcinoma, supraclavicular lymph node metastasis represents an uncommon, but clinically significant finding that can lead to changes in treatment planning. PET imaging represents a valuable tool in the detection and follow up of these patients. Image: PET/CT scans before and after chemotherapy.